2007
DOI: 10.1111/j.1530-0277.2007.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Attention‐Deficit Hyperactivity Disorder Moderates the Life Stress Pathway to Alcohol Problems in Children of Alcoholics

Abstract: Background-Parent alcoholism is a well-established risk factor for the development of pathological alcohol involvement in youth, and life stress is considered to be one of the central mechanisms of the parent alcoholism effect; however, little is known about the moderators of the life stress pathway. Attention-deficit hyperactivity disorder (ADHD) has also been shown to predict pathological alcohol involvement, however, little is known about whether or not ADHD interacts with parent alcoholism to increase offs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 72 publications
0
12
1
Order By: Relevance
“…In addition, there was a positive correlation between ADHD in adolescents and pathologic alcohol use. Based on these findings, the authors proposed a hypothesis that ADHD can moderate the life stress pathways and thus promote transition of paternal alcoholism to child's pathologic involvement with alcohol 22 Investigating the hypothesis that ADHD confers an increased risk of heavy drinking in later adolescence, Molina and colleagues 23 compared 364 children diagnosed with ADHD with a control group of 240 age-matched non-ADHD adolescents and young adults at baseline and again after 8 years. The investigators found that rates of heavy drinking, drunkenness, symptoms of alcohol use, and alcohol use disorders were elevated in 15-to 17-year-old adolescents with ADHD but not in younger ADHD adolescents.…”
Section: Alcoholtobacco Smoking and Caffeine Alcoholmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, there was a positive correlation between ADHD in adolescents and pathologic alcohol use. Based on these findings, the authors proposed a hypothesis that ADHD can moderate the life stress pathways and thus promote transition of paternal alcoholism to child's pathologic involvement with alcohol 22 Investigating the hypothesis that ADHD confers an increased risk of heavy drinking in later adolescence, Molina and colleagues 23 compared 364 children diagnosed with ADHD with a control group of 240 age-matched non-ADHD adolescents and young adults at baseline and again after 8 years. The investigators found that rates of heavy drinking, drunkenness, symptoms of alcohol use, and alcohol use disorders were elevated in 15-to 17-year-old adolescents with ADHD but not in younger ADHD adolescents.…”
Section: Alcoholtobacco Smoking and Caffeine Alcoholmentioning
confidence: 98%
“…21 For children with ADHD, problems with alcohol can begin at an early age and may moderate life stress pathways that appear to contribute to risk of alcoholism. Marshal and colleagues 22 investigated the drinking behavior of 142 adolescents with a childhood ADHD diagnosis and 100 matched control adolescents without childhood ADHD. At least 1 parent of each child was interviewed.…”
Section: Alcoholtobacco Smoking and Caffeine Alcoholmentioning
confidence: 99%
“…Other researchers have replicated this fi nding numerous times, and conduct disorder (CD) has emerged as one of the most robust childhood predictors of alcohol disorders (Kuperman et al, 2001a;Robins, 1999). Two other externalizing conditions, attention defi cit-hyperactivity disorder (ADHD) and oppositional defi ant disorder (ODD), also have been identifi ed as precursors of problematic alcohol and drug involvement, although fi ndings have been less consistent (Disney et al, 1999;Elkins et al, 2007;Marshal et al, 2007;Molina and Pelham, 2003;White et al, 2001).…”
mentioning
confidence: 99%
“…These issues are what make them different from the general population, who do not experience this family situation. In the literature, there are several studies on this, which point to situations such as behavioral problems, symptoms of internalization, Attention-Deficit Hyperactivity Disorder (ADHD) and family cohesion, among other things (EIDEN; EDWARDS; LEONARD, 2007;TRIM et al, 2007;MARSHAL et al, 2007;LEV-WIESEL;LIRAZ, 2007;KELLEY et al, 2007;LORBER et al, 2007), all of them objects for further investigation.…”
Section: 10% (N=365)mentioning
confidence: 99%